Study on the correlation between alkaloids and tastes of Coptis Rhizome from four species based on UHPLC-QQQ-MS/MS combined with electronic tongue technique - Huang, Yufeng; Luo, Wenhui; Pei, Wenhan; Sun, Dongmei; Zhou, Hua; He, Fan (Frontiers in Plant Science, 2024)
Objective: Taste is one of the vital indicators for the quality evaluation of Coptis rhizome (CR), but the traditional taste evaluation lacks objectivity. By establishing the correlation between CR's tastes and alkaloids, an objective basis for the taste evaluation was established. Methods: Ultra-high performance liquid chromatography tandem triple quadrupole mass spectrometry (UHPLC-QQQ-MS/MS) and electronic tongue technique were performed to determine ten alkaloid contents and eight tastes from Coptis chinensis rhizome, Coptis deltoidea rhizome, Coptis teeta rhizome, and Coptis japonica rhizome, respectively. Combined with multivariate statistical analysis, we established models to discriminate the alkaloid contents and tastes of CR, screened the differential alkaloids and tastes, and performed Pearson's correlation analysis on the results of alkaloids and tastes. Results: 1) According to the previous UHPLC-QQQ-MS/MS method established by our research group, the contents of ten alkaloids of the four species of CR were quantified, of which jatrorrhizine, columbamine, and magnoflorine were the differential alkaloids of the four species. 2) The electronic tongue technique realized the objectification of CR's tastes and distinguished the species of CR based on the tastes of aftertaste-A, sourness, bitterness, and richness. 3) Pearson's correlation analysis shows the bitterness of CR was mainly manifested as aftertaste-B, indicating the higher the aftertaste-B value, the higher the berberrubine content. Astringency and aftertaste-A could be suggested as quality evaluation indexes of CR, due to the positively correlated or significantly positively correlated with coptisine, epiberberine, berberine, and palmatine, respectively. Conclusion: Electronic tongue technique has successfully achieved the objectification of the tastes of CR, and combined with UHPLC-QQQ-MS/MS technique for alkaloid quantification and correlation research, it provides a new idea for the quality evaluation of CR.